3D finite elements method (FEM) Analysis of basic process parameters in rotary piercing mill - Z. Pater; J. Bartnicki; J. Kazanecki (Metalurgija, 2012)
In this paper 3D FEM analysis of process parameters and its infl uence in rotary piercing mill is presented. The FEM analyze of the rotary piercing process was made under the conditions of 3D state of strain with taking into consideration the thermal phenomena. The calculations were made with application of different rolls’ skew angles and different plug designs. In the result, progression of shapes, temperature and distributions of stress and strain were characterized. The numerical results of calculations were compared with results of stand test with use of 100Cr6 steel. The comparisons of numerical and experimental tests confirm good agreement between obtained results.